Utilization of Information Sources by SRI growers - Meenakshi Gabhane , M. K. Dubey, D. K. Singh and Anjani Kumar, (Indian Journal of Extension Education, 2015)
The information sources play a key role in ensuring food security and sustainable agriculture. The demonstration,agricultural scientist, friend, extension worker, training, television, radio, relative etc. are the main source of informationby creating socio information support system to identify the problem of the SRI farmers so that the need based informationthrough information sources may be provided and also to established its utility among SRI farmers there by resulting. Thepresent study was carried out to know the utilization of information sources by SRI growers in Balaghat block of DistrictBalaghat Madhya Pradesh with 120 SRI farmers of Balaghat block. It was found that the most of the respondents theywere utilized the information sources mostly respect to SRI method of paddy cultivation, In case of individual contactmethods Agricultural scientists and Rural Agril. Extension officers were the main source of information. In case of groupapproach Demonstration, Training and Lecture were the main source of information and in the case of mass approachTelevision and Radio were the main source of information utilized by the SRI growers.